The Influence of Electronic Word of Mouth and Influencer Personal Branding on Umrah Package Purchase Decisions through Consumer Trust - Alia Rogayah; Heri Setiawan; Alditia Detmuliati (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This study seeks to investigate how electronic word of mouth and influencer personal branding shape consumers' decisions to purchase Umrah packages, with consumer trust positioned as the variable mediating this relationship, using PT FAS in Palembang as the research setting. Method: A quantitative survey design was applied in this research to examine the relationships proposed in the conceptual framework. Information was obtained from 237 respondents through a structured questionnaire, which involved individuals who had previously undertaken umrah in purchasing umrah services from an umrah travel agency in Palembang. Data analysis relies on the PLS-SEM framework. The evaluation process included testing the measurement model to determine whether each construct met the required criteria of validity and reliability, followed by structural model analysis to assess the link among the examined variables. The study also applied hypothesis testing and mediation assessment to identify the direct pathways and indirect relationships within the research model. Result: The results denote that electronic word of mouth and influencer personal branding are unable to directly explain variations in purchase decisions at a statistically significant level. Nevertheless, both factors contribute positively to the formation of consumer trust. The analysis further indicates that consumer trust becomes an important factor influencing purchase decisions and acts as an intermediary pathway through which E-WoM and Influencer Personal Branding affect the decision-making process for Umrah package purchases. Contribution: This research extends existing knowledge in tourism and digital marketing by highlighting the pivotal mediating role that consumer trust plays in connecting electronic word of mouth and influencer personal branding with purchase decisions in the Umrah travel industry. The results also have practical implications for Umrah travel agencies seeking to develop effective digital marketing strategies that foster consumer trust and drive stronger purchasing decisions.